(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: The frequency of Extended Spectrum Beta-Lactamase (ESBL) producing bacteria among clinical isolates is a serious global health concern that has complicated treatment strategies and is very alarming. So the reporting of ESBLproducing Gram negative bacteria from the clinical samples will be useful for the clinician to select the appropriate antibiotics and to take proper precaution for prevention of these resistant organisms. To study the prevalence of ESBL producers among the Gram negative bacteria and antibiotic susceptibility pattern of these isolates. Materials and methods: This cross sectional study was carried out in the Department of Microbiology of a tertiary care hospital, Chattogram from January 2021 to December 2021. A total of ninety consecutive, nonrepetitive, Gram negative isolates were selected as confirmed ESBL producers, detected by Phenotypic Confirmatory Disc Diffusion Test (PCDDT). Antibiotic susceptibility test was performed on Mueller Hinton agar plate by Kirby Bauer Disc Diffusion method. Results: Out of 300 isolates, 90 (52.63%) were found to be ESBL producers by PCDDT. The isolates of Pseudomonas spp. (37.77%) were the most common ESBL producing bacteria followed by Klebsiella spp. (28.88%), Escherichia coli 39 (22.22%) and others. Maximum (47.93%) ESBL producing bacteria were isolated from woundswab followed by urine (26.44%). Most ESBL producers were resistant to commonly used antibiotics. Amikacin (80%), pipercillin-tazobactam(75%) and meropenem (73%) were the most effective agents for the treatment of ESBL producing bacteria. Conclusion: The findings of this study emphasize the need for a continuous surveillance such as detection of ESBL along with routine susceptibility test will help the clinician to give a strict guideline for antibiotic therapy and reduce the increasing burden of antibiotic resistance. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 45-48